How Catholic was Augustine? Confessional Patristics and the Survival of Erasmus in the Counter-Reformation - Visser, Arnoud S. Q. (The journal of ecclesiastical history, 2010)
This article explores the impact of Catholic confessionalism on humanist scholarship by focusing on the edition of Augustine of Hippo's collected works produced by the Leuven theologians in 1577–8. This edition replaced Erasmus' controversial version and claimed to provide an authoritative, Catholic text. Yet an analysis of the paratextual presentation shows that the result was a neutralised Augustine, rather than a paragon of Tridentine Catholicism. The editors avoid controversial theology, while silently copying substantial parts of Erasmus' censurae and marginal notes. Local politics and publishing interests explain the intriguing survival of Erasmus and exemplify the disparate implementation of Trent in Catholic Europe.